Keakuratan Kode Kombinasi Dokumen Rekam Medis Pasien Rawat Inap Jaminan Kesehatan Nasional Di Rumah Sakit Umum Daerah Pandan Arang Boyolali - Linda Widyaningrum; Hanggargita Nur Wahyuningsih; Astri Sri Wariyanti (Universitas Duta Bangsa Surakarta, 2022)
Coding is an important role in the implementation of health financing for the National Health Insurance. Implementation of the provision of diagnostic codes in health services must pay attention to coding rules to produce accurate data and information. This study aims to determine the accuracy of the combined category code of medical record documents for inpatients with national health insurance at Pandan Arang Hospital Boyolali. Method of non-experimental research with descriptive analysis. The approach used is retrospective with observation and interview data collection. The sample used was 98 national health insurance inpatient medical records using purposive random sampling technique with inclusion and exclusion criteria. The procedure for assigning a diagnostic code to the combination category is in accordance with the existing SOP. The accuracy of the diagnostic code for the combination category is 64% (63 documents) and 36% (35 documents) is not accurate due to an error in code selection (35 documents). The factors causing the inaccuracy of the diagnostic code for the combination category based on ICD-10 are medical personnel, medical record personnel (coder) and code selection errors. Researchers suggest that hospitals should make standard operating procedures to doctors regarding writing diagnoses with complete medical information this will minimize errors in coding combination categories. Coding officers should look at the results of supporting examinations and patient progress records in order to provide an accurate diagnosis of the code.